Selection of suitable formula for manufacturing meat analogue supplemented with white kidney bean flour and Jerusalem artichoke flour - Weeraya Sreeitthiyawet; Orawan Oupathumpanont; Phantipha Charoenthaikij (Penerbit Universiti Kebangsaan Malaysia, 2019)
This research aimed to study: 1) the suitable formula of meat analogue supplemented with white kidney bean flour and Jerusalem artichoke flour, 2) the chemical and physical properties of the supplemented meat analogue, and 3) the consumer acceptance. The experiment was designed by a mixture design approach and the following three parameters were included: 30–45% of white kidney bean flour, 20–30% of Jerusalem artichoke flour and 35–40% of soybean flour, resulting in 9 formulas. K-Mean cluster analysis of the 9 formulas showed that formula 1, 3, 5 and 6 produced high cutting force and shear force. Among these four, the most suitable formula was the 6th which contained 40% of white kidney bean, 22.5% of Jerusalem artichoke flour and 37.5% of soybean flour, while the cutting force, shear force, aw and moisture content of the supplemented meat analogue from this formula were at 5.98 ± 0.71, 19.26 ± 0.50, 0.52 ± 0.01 and 3.53% ± 0.20, respectively. Most consumers’ overall liking parameter of the supplemented meat analogue was at the very like level.